PENGARUH PENDIDIKAN INKLUSIF DAN MOTIVASI GURU TERHADAP KETERAMPILAN KEPEKAAN SOSIAL SISWA BERKEBUTUHAN KHUSUS DI SD NEGERI SE-KOTA TERNATE - Basyir, Rahma N; Hasan, Said; Haerullah, Ade; Ahmad, Iswadi M (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
This study aims to analyze the influence of inclusive education and teacher motivation on the social sensitivity skills of students with special needs in public elementary schools throughout Ternate City. This study with a quantitative approach uses data analyzed through regression tests. The results of the study indicate that inclusive education has a significant and positive influence on the social sensitivity skills of students with special needs, as evidenced by a significance value of 0.001 (<0.05). In addition, teacher motivation is also proven to have a significant and positive influence on the social sensitivity skills of students with special needs, with a significance value of 0.004 (<0.05). Simultaneously, inclusive education and teacher motivation together provide a significant and positive influence on the social sensitivity skills of students with special needs, with a significance value of 0.030 (<0.05). This finding implies the importance of implementing quality inclusive education and increasing teacher motivation in developing the social sensitivity skills of students with special needs.